Employee Retention Implementation Prevents Employee Turnover - Trisna Wijayanthi, Ida Ayu; Subagio, Mochammad; Suhendra, Agus; Hartini, Hartini; Amin Darmawan, Alfais (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The purpose of this study is to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of human resource management. The article on the application of employee retention in preventing employee turnover is a scientific literature article within the scope of the research methodology. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or conduct a review of relevant previous articles. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and is sourced from online academic media such as the Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Emerald, Sage, WoS, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this article's literature review are: 1) Employee Retention affects Employee Turnover; 2) Career Path affects Employee Turnover; 3) Organizational Commitment affects Employee Turnover; and 4) Job Satisfaction affects Employee Turnover.